AI in Relation to Water Management: A Legal-Constitutional Approach to Socio-Spatial Justice and the Rights of Nature - Arguello Escobar, Sebastian Fernando; Córdova Cortez, Christian Andrés; Castillo Garzón, Byron Geovanny (Universidad Hemisferios, 2026)
The emergence of artificial intelligence (AI) in water governance configures an unprecedented constitutional paradox: while its applications promise to optimize the monitoring and distribution of water, its computational infrastructure demands growing volumes of this resource, creating tensions with the principles of Ecuadorian ecological constitutionalism. This paper examines, drawing on the thought of Boaventura de Sousa Santos and the theoretical frameworks of cognitive justice and legal pluralism, the compatibility between such technological incorporation and the Ecuadorian legal order. Methodologically, it articulates a systemic-structural-functional approach with a hermeneutic-critical method and a comparative jurisprudential analysis (United States, Chile, and Ecuador), complemented by recent empirical evidence on water consumption in data centers. The findings suggest that AI reproduces extractivist logics when operating outside local and indigenous knowledge systems, generates substantive tensions with the human right to water (art. 12 of the Ecuadorian Constitution), the rights of nature (arts. 71-74), and the precautionary principle, and that the Ecuadorian legal system provides suitable jurisdictional remedies to safeguard such rights against technological risks. Consequently, a plural water governance model is proposed, grounded in the dialogue of knowledge, intercultural co-responsibility, and constitutional enforceability, as a pathway for the epistemological and normative reconstruction of environmental law oriented toward the common good and ecosystem balance.